INTEGRASI SISTEM INFORMASI AKADEMIK TERPADU (SIAKAT) DENGAN FEEDER PDDIKTI - Erni Widarti; Saiful Bahri; Agus Widyanto (Universitas Boyolali, 2018)
The title of this research is the integration of Integrated Academic Information System (SIAKAT) with PDDIKTI Feeder. The place used to conduct this study at the University of Boyolali. The study was conducted over three months starting from November 1, 2015 until the date of February 1, 2016. Systems at the University of Boyolali there is currently no service applications that can automatically integrate the data of students, lecturer, courses, card of study, the value is directly between the data in the Integrated Academic Information System (SIAKAT) University Boyolali to PDDIKTI Feeder. To overcome these problems it, so will build an application will be titled Integrated Academic Information System Integration (SIAKAT) to Feeder PDDIKTI using Web Service Case studies of Boyolali University . These applications will be designed using the programming language PHP and MySQL as the database. This application is capable of synchronizing the data and hopefully this application can help minimizing the time in data reporting SIAKAT University of Boyolali to Feeder PDDIKTI